The Safety and Efficacy of Weighted Baseballs - Michael M Reinold; Leonard C Macrina (International Journal of Sports Physical Therapy)
One of the most common methods of training to enhance pitching velocity is the use of weighted baseballs. As with anything else, the excitement and popularity often proceed our scientific understanding.